Cranberry Proanthocyanidins Improve Intestinal sIgA During Elemental Enteral Nutrition. (28th January 2013) - Pierre, Joseph F.; Heneghan, Aaron F.; Feliciano, Rodrigo P.; Shanmuganayagam, Dhanansayan; Krueger, Christian G.; Reed, Jess D.; Kudsk, Kenneth A.
Abstract : Background : Elemental enteral nutrition (EEN) decreases gut‐associated lymphoid tissue (GALT) function, including fewer Peyer's patch lymphocytes and lower levels of the tissue T helper 2 (Th2) cytokines and mucosal transport protein polymeric immunoglobulin receptor (pIgR), leading to lower luminal secretory immunoglobulin A (sIgA) levels. Since we recently demonstrated that cranberry proanthocyanidins (PACs) maintain the Th2 cytokine interleukin (IL)–4 when added to EEN, we hypothesized the addition of PACs to EEN would normalize other GALT parameters and maintain luminal levels of sIgA. Methods : Institute of Cancer Research mice were randomized (12/group) to receive chow, EEN, or EEN + PACs (100 mg/kg body weight) for 5 days, starting 2 days after intragastric cannulation. Ileum tissue was collected to measure IL‐4 by enzyme‐linked immunosorbent assay, pIgR by Western blot, and phosphorylated STAT‐6 by microarray. Intestinal wash fluid was collected to measure sIgA by Western blot. Results : Compared with chow, EEN significantly decreased tissue IL‐4, phosphorylated STAT‐6, and pIgR. The addition of PACs to EEN prevented these alterations. Compared with chow, EEN resulted in significantly lower levels of luminal sIgA. The addition of PACs to EEN increased luminal sIgA levels compared with EEN alone. Conclusions : This study suggests the addition of PACs to EEN may support GALT function and maintain intestinal sIgA levels compared with EEN administration alone.